2021
DOI: 10.1093/police/paab016
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Young Drivers’ Perceptions of Procedurally Just Policing

Abstract: The procedural justice approach to policing may be an effective method of reducing young driver noncompliance with traffic laws. We undertook a qualitative study in two Australian states (Queensland and Victoria) to explore how procedural justice operates when police interact with young drivers. Metropolitan and regional focus groups were conducted (n = 31, 45% male, 17–25 years), and transcripts coded against the four procedural justice elements: (a) neutrality, (b) respect, (c) voice, and (d) trust. Young dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Others have demonstrated that the quality of interactions with the police influence perceptions of trust and legitimacy (e.g., Fagan & Piquero, 2005), yet it is less clear how, specifically, these attributes influence—either positively or negatively—perceptions of trust during interactions. Although there is a large social psychological literature on the effect of different aspects of procedural justice, for example, this largely relies on lab-based studies and has not been consistently applied to “real-world” policing contexts (for a recent exception see Bates et al, 2021). Further research is required to investigate the interpretations and meanings which are assigned to these (trustee) attributes by young people in specific local contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Others have demonstrated that the quality of interactions with the police influence perceptions of trust and legitimacy (e.g., Fagan & Piquero, 2005), yet it is less clear how, specifically, these attributes influence—either positively or negatively—perceptions of trust during interactions. Although there is a large social psychological literature on the effect of different aspects of procedural justice, for example, this largely relies on lab-based studies and has not been consistently applied to “real-world” policing contexts (for a recent exception see Bates et al, 2021). Further research is required to investigate the interpretations and meanings which are assigned to these (trustee) attributes by young people in specific local contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Procedural justice theory stipulates that a perceived fair legal process builds a high perception of the legitimacy in the law, which leads to more compliant behaviours from members of the public (Barkworth & Murphy, 2015;Bradford et al, 2015;Dai et al, 2011;Murphy & Tyler, 2008). Within procedural justice, there are four elements; voice, neutrality, respect, and trustworthiness (Bates et al, 2020;Goodman-Delahunty, 2010;Sargeant et al, 2012). This study heard the experiences of MCUs and examined them in alignment with the four pillars of procedural justice to understand the continued drug driving offending from MCUs.…”
Section: Introductionmentioning
confidence: 99%